2004
DOI: 10.1023/b:appt.0000038037.68908.6e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of histone deacetylase inhibitor Trichostatin A induced apoptosis in human osteosarcoma cells

Abstract: Although histone deacetylase (HDAC) inhibitors are emerging as a promising new treatment strategy in malignancy, how they exert their effect on osteosarcoama cells is as yet unclear. This study was undertaken to investigate the underlying mechanism of a HDAC inhibitor Trichostatin A (TSA)-induced apoptosis in a osteosarcoma cell line HOS. We observed that TSA treatment decreased the viability of the cells and prominently increased acetylation of histone H3. Evidence was obtained indicating that TSA induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 26 publications
1
35
1
2
Order By: Relevance
“…Treatment with HDAC inhibitors triggers both the intrinsic pathways and sensitizes tumor cells to the death ligands that initiate the extrinsic pathway of apoptosis. NaB, TSA, and MS-275 have been reported to induce mitochondrial permeability transition with a subsequent release of proapoptotic cytochrome c into the cytosol, resulting in activation of caspase-9 and caspase-3, thereby executing apoptosis (Rosato et al 2001, Maggio et al 2004, Roh et al 2004. Additionally, HDAC inhibitor treatment has been shown to upregulate proapoptotic Fas, a member of the tumor necrosis factor receptor superfamily and the tumor necrosis factorrelated apoptosis-inducing ligand receptors/death receptors DR4 and DR5, thereby triggering the extrinsic pathway, and further downregulate FLICE (caspase-8)-inhibitory protein c-FLIP, leading to caspase-8 and subsequently to caspase-3 activation (Bhalla & List 2004, Natoni et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with HDAC inhibitors triggers both the intrinsic pathways and sensitizes tumor cells to the death ligands that initiate the extrinsic pathway of apoptosis. NaB, TSA, and MS-275 have been reported to induce mitochondrial permeability transition with a subsequent release of proapoptotic cytochrome c into the cytosol, resulting in activation of caspase-9 and caspase-3, thereby executing apoptosis (Rosato et al 2001, Maggio et al 2004, Roh et al 2004. Additionally, HDAC inhibitor treatment has been shown to upregulate proapoptotic Fas, a member of the tumor necrosis factor receptor superfamily and the tumor necrosis factorrelated apoptosis-inducing ligand receptors/death receptors DR4 and DR5, thereby triggering the extrinsic pathway, and further downregulate FLICE (caspase-8)-inhibitory protein c-FLIP, leading to caspase-8 and subsequently to caspase-3 activation (Bhalla & List 2004, Natoni et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Although TSA is reported to inhibit cell growth and induce apoptosis of various cancer cells (Roh et al, 2004;Yee et al, 2004), there is little evidence of its pharmacologic efficacy on lung cancer cells. Choi demonstrated that TSA induces apoptotic death of A549 lung cancer cell (Choi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…13B). The mass difference between the y 14 -and the y 13 lation, the chain length of chemically synthesized peptide substrates, and the generation of artificial acetylation sites by peptide mutations. Regarding the identification of enzymatically acetylated residues in peptides or proteins the disregard of the non-enzymatic cysteine acetylation can lead to false-positive results.…”
Section: Fig 3 Strategies For the Identification Of Acetylation Sitmentioning
confidence: 99%
“…The reverse reaction is catalyzed by deacetylases that remove acetyl groups from specific acetyllysine residues in their substrates. The reversible lysine acetylation of histones and nonhistone proteins plays a vital role in the regulation of many cellular processes including chromatin dynamics and transcription (2)(3)(4)(5), gene silencing (6,7), cell cycle progression (8 -11), apoptosis (12)(13)(14), differentiation (15)(16)(17)(18)(19), DNA replication (20,21), DNA repair (22)(23)(24)(25)(26)(27), nuclear import (28 -30), and neuronal repression (31)(32)(33). More than 20 acetyltransferases and 18 deacetylases have been identified so far, but the mechanistic details of substrate selection and site specificity of these enzymes remain unclear.…”
mentioning
confidence: 99%